2020
DOI: 10.31893/jabb.20015
|View full text |Cite
|
Sign up to set email alerts
|

Handling, reactivity and price of beef cattle

Abstract: Given the importance of cattle breeding for the Brazilian economy, as well as the growing concern with animal welfare, studies that clearly and objectively approach the way cattle are handled during auctions become necessary. This study aims, hence, at assessing the influence of cattle handling on the reactivity of animals at the time of arrival at the exhibition park. We also aimed to evaluate the impact of reactivity and visual aspects on the price for animals at auctions in the northern region of the state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The PCA results also showed that kicking and vocalization contributed the least to the variation in the analysis (Figure 1 and Table 5). In this line, studying the reactivity of beef cattle arriving at an expo event, Carvalho et al (2020) observed a low incidence of vocalization, defecation, and urination. Investigating the variability of vocal and behavioral responses to the (1) REAC, reactivity score at 20 s (points); MOV_10 and MOV_20, movement scores at 10 and 20 s, respectively; TEN_10 and TEN_20, tension scores at 10 and 20 s, respectively; BRE_10 and BRE_20, breathing scores at 10 and 20 s, respectively; VOC_10 and VOC_20, vocalizing scores at 10 and 20 s, respectively; KICK_10 and KICK_20, kicking scores at 10 and 20 s, respectively; and FS, flight speed from cattle crush (m s -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PCA results also showed that kicking and vocalization contributed the least to the variation in the analysis (Figure 1 and Table 5). In this line, studying the reactivity of beef cattle arriving at an expo event, Carvalho et al (2020) observed a low incidence of vocalization, defecation, and urination. Investigating the variability of vocal and behavioral responses to the (1) REAC, reactivity score at 20 s (points); MOV_10 and MOV_20, movement scores at 10 and 20 s, respectively; TEN_10 and TEN_20, tension scores at 10 and 20 s, respectively; BRE_10 and BRE_20, breathing scores at 10 and 20 s, respectively; VOC_10 and VOC_20, vocalizing scores at 10 and 20 s, respectively; KICK_10 and KICK_20, kicking scores at 10 and 20 s, respectively; and FS, flight speed from cattle crush (m s -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The high concentrations of cortisol in species subjected to stressors, can be caused by energetic stress and the increased levels of cortisol and glucose seen as simultaneous physiological responses (Grandin, 2016), together with the relationship to the environment and the handling routines (Carvalho et al, 2020). As such, the results of the present study, which showed lower levels of glucose and cortisol over time in the animals submitted to GHP, indicate a reduction in the stress levels of these animals throughout the experimental period; whereas the lack of reduction in both physiological indicators in animals subjected to THS, show that such practices act as a stressor.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates that cattle are able to memorise the handling they receive (Ceballos et al, 2016(Ceballos et al, , 2018 and by means of these experiences, react adversely or favourably when exposed to these experiences again. The more reactive the animal, the greater the concentration of plasma cortisol during moments which are different to its natural environment or to the type of handling used against it (Carvalho et al, 2020;Moura et al, 2021). Plasma glucose concentrations, on the other hand, increase during moments of peak stress (Carvalho et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the positive correlation between RS and TS highlights the influence of the individual temperament of the animals on their response during weighing. This suggests that more reactive animals tend to show a greater emotional response and a more aggressive temperament during weighing, which can affect their tranquility and well-being during handling [ 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%